Thermal Analysis of a Parabolic Trough Collectors System Coupled to an Organic Rankine Cycle and a Two-Tank Thermal Storage System: Case Study of Itajubá-MG Brazil (2022)
settingsOrder Article Reprints Open AccessArticle Thermal Analysis of a Parabolic Trough Collectors System Coupled to an Organic Rankine Cycle and a Two-Tank Thermal Storage System: Case Study of Itajubá-MG Brazil by Gaylord Carrillo Caballero 1,2,Yulineth Cardenas Escorcia 3,Luis Sebastián Mendoza Castellanos 4,Ana Lisbeth Galindo Noguera 4,Osvaldo José Venturini 2,Electo Eduardo Silva Lora 2,Elkin I. Gutiérrez Velásquez 5 andAnibal Alviz Meza 6,*ORCID 1 Research Group en Energías Alternativas y Fluidos (EOLITO), Universidad Tecnológica de Bolívar (UTB), Cartagena 130002, Colombia 2 Excellence Group in Thermal Power and Distributed Generation-NEST, Institute of Mechanical Engineering, Universidade Federal de Itajubá, Itajubá 37500-000, Brazil 3 Research Group GIOPEN, Energy Department, Universidad de la Costa (CUC), Barranquilla 080016, Colombia 4 Research Group in Resources, Energy and Sustainability (GIRES), Faculty of Energy Engineering, Universidad Autónoma de Bucaramanga (UNAB), Bucaramanga 680008, Colombia 5 Faculty of Mechanic, Electronics and Biomedical Engineering, Universidad Antonio Nariño, Medellin 050005, Colombia 6 Research Group en Deterioro de Materiales, Transición Energética y Ciencia de datos DANT3, Facultad de Ingeniería, Arquitectura y Urbanismo, Universidad Señor de Sipán, Chiclayo 14002, Peru * Author to whom correspondence should be addressed. Energies 2022, 15(21), 8261; https://doi.org/10.3390/en15218261 Received: 5 October 2022 / Revised: 28 October 2022 / Accepted: 31 October 2022 / Published: 4 November 2022 Download Browse Figures Versions Notes Abstract This study examined an Organic Rankine Cycle powered by a parabolic trough collector and a two-tank thermal storage system based on the development of a mathematical model, for the conditions of the city of Itajubá in Brazil. First, geometrical optics and heat transfer models of the collector–receiver set were used to determine the thermal equilibrium of the solar thermal collector system and parameters such as the efficiency of the solar field, heat and optical losses, and thermal energy of the outlet fluid. Next, the thermal equilibrium of the Organic Rankine Cycle was found in order to establish its operational parameters. Finally, the behavior of the thermal storage system was analyzed through its modeling. Once the characterization of the storage system was completed, the integrated operation of the proposed system was evaluated. Given Itajubá’s weather conditions, the results indicate that an electricity generation system can be implemented with the Solel UVAC Cermet selective coating for the absorber tube, water as the heat transfer fluid, and R-245fa as the working fluid. Based on the solar irradiation profile (1 March 2019), the parabolic trough collectors provided 63.3% of the energy required by the Organic Rankine Cycle to generate 7.4 kW, while the thermal storage system provided 36.4% of the energy demanded by the power generation block. Additionally, the results demonstrate the main conclusions that the turbine’s efficiency was influenced by parameters such as rotational speed, which is affected by the turbine inlet temperature, which, in turn, depends on the behavior of the solar irradiation profile onsite.